Amendments to the Constitution of the Czech Republic - Jirásek, Jiří (Acta Universitatis Lodziensis. Folia Iuridica, 2018)
The Constitution of the Czech Republic was approved on 16th december 1992. The regulation of the constitutional relations in the Czech Republic is includedin more constitutional laws, which are called in the Constitution in Article 112 „constitutional order“. Since 1993 the Constitution was changed 9, besides there were presented many other proposals of the constitutional laws for changes of the Constitution, which failed to approve.